Review of Irish Liberty, British Democracy: The Third Home Rule Crisis, 1909-14, by James Doherty - Angus Mitchell (Review of Irish Studies in Europe)
Review of Irish Liberty, British Democracy: The Third Home Rule Crisis, 1909-14, by James Doherty (Cork: Cork University Press, 2019) ISBN: 9781782053606,320pp. €39.00 (hardback).